Educação não-formal em mídias: divulgação científica sobre nanotecnologia - Körbes, Clecí (2013)
Over the last decade, public policies for science and technology popularization have been institutionalized in Brazil. However, there are a limited number of studies on the methodologies used and the contents developed. In this context, the central goal of this thesis is to examine the scientific popularization on nanotechnology in different media that respond to interests and values of different social groups, and to investigate, through a comparative analysis, the characteristics of the science popularization models utilized by these media, the contents addressed and those absent, and their educative function. The methodological approach consists of a content analysis, both qualitative and quantitative, based on the Social Studies of Science and Technology, particularly the Latin American strands, and the studies on non-formal education. The thesis analyzes the Science sections of the open television program Bom Dia Brasil and the newspaper Folha de S. Paulo produced during the period 2008-2010, and a non-aleatory 20% sample of the webTV interview show Nanotecnologia do Avesso exhibited during 2009-2010. The comparative analysis showed that definitions of nanotechnology considerably vary among the media, depending on who produced them and the circumstances that led to their enunciation and stabilization. In Bom Dia Brasil and Folha de S. Paulo the concept of nanotechnology emphasizes the material artifact, providing scarce information on its socio-technical configuration, while the latter aspect is widely addressed by the program Nanotecnologia do Avesso. All the media describe the new properties and functions of the matter in the nanoscale, but differ in the way they do it, according to the interests of the relevant actors represented, some highlighting the potential for innovation that stems from such properties; other stressing the new risks they entail. Bom Dia Brasil and Folha de S. Paulo emphasize the promises and benefits of these new properties and functionalities, such as more efficient products that will open up new markets, advances in health research and quality of life, and environmental preservation. Such visions reproduce discourses based on linear models that stress the neutrality, inexorability and continuous progress of science and technology. In Nanotecnologia do Avesso is preeminent the discussion on potential risks and social, legal and ethical implications of nanotechnology, and the demand for the application of the precautionary principle and mandatory regulation. The conclusion of the thesis is that science popularization on nanotechnology is an educational process full of tensions and polarizations that transcends its specificity of symbolic practice and is articulated to the broader social and productive practice, sometimes approaching, sometimes deviating from the sociotechnical citizenship perspective, depending on the popularization models that are used and the social groups that are represented.